A comprehensive numerical model for kerf width prediction in hot wire cutting of expanded polystyrene. (January 2021) - Karmakar, N.; Subbiah, S.
Abstract: Improving accuracy in cutting of expanded polystyrene (EPS) foam using hot wire depends on understanding and controlling the kerf width, which in turn depends on temperature distribution in the foam during cutting. We present here a comprehensive temperature-validated numerical thermal model that incorporates important factors such as convective heat transfer between the wire and molten/ablated foam and the surroundings, thermal coupling between the wire and EPS, temperature dependent EPS foam and wire properties and the latent heat of melting and ablation of EPS, to predict the three-dimensional temperature distributions in the EPS foam in the region immediately around the hot wire and across the entire width of the EPS foam being cut. Based on isothermal temperature contour at the melting point of the foam, kerf width is predicted and compared with experimental measurements. Average kerf width and kerf width variation across the width of the work are seen to be predicted reasonably by the model. The barrelling of the cut profile due to the variation of wire temperature along its length is also quantified and compared with experiments. Selectively switching off various model parameters such as temperature dependent EPS and wire properties and the thermal coupling between wire and EPS shows significant contributions of these factors towards the error in kerf width predictions. Convective heat losses are found to be important when the width of EPS being cut is less such as in thin sheets. As confirmed by experimental data, kerf width is higher near the work edges and stays constant within the bulk region of the work. The model developed comprehensively captures the thermal effects and thus can be used to improve precision while cutting EPS shapes.